Spatial impulse response method for predicting pulse-echo fields from a linear array with cylindrically concave surface - Wu, P (IEEE transactions on ultrasonics, ferroelectrics, and frequency control, 1999)
This paper is intended to apply the spatial impulse response method (SIRM) to predict the pulsed-echo fields radiated by a linear array with a cylindrically concave surface. To this end, an approach to computing the spatial impulse response (SIR) of a cylindrically curved, rectangular aperture is proposed. The approach obtains the SIR by applying coordinate transform and then superposing the SIRs of a row of narrow strips into which the aperture is divided in one direction (in which the aperture is curved). The strips are so narrow that they can be considered planar, rectangular apertures whose exact SIRs are available in analytic form. In a special case where the field points are on the center axis of the cylindrical curve, the analytic form of the SIR of the curved, rectangular aperture is found. The SIR of a linear array with a cylindrically concave surface is then obtained using the approach. The pulsed-echo fields from the array (i.e., those radiated by the array, diffracted by a point-like scatterer, and received by the same array) are further simulated and have been measured using a point-like scatterer. The simulated and the measured results are compared, and the comparison shows that the simulated and the measured results are in very good agreement